Insect Management for Celery and Parsley - Susan E. Webb (EDIS, 2002)
Celery and parsley (and carrots, treated in another chapter) are related crops in the family Apiaceae (Umbelliferae). Both fall in EPA Crop Group 4, Leafy vegetables. To a large degree they share insect pests and are thus treated together here. Most of the information presented refers only to celery, but pest biology and management options can, in most cases, be applied to parsley. Other related leafy vegetables, for which we do not have specific pesticide tables, include Florence fennel (finochio), and chervil. Key insect pests are described in this document with additional management options. Pesticides registered for use on celery and parsley are listed in two separate tables at the end of this document. Many other insects may occasionally attack these crops but seldom cause economic damage. This document is ENY-463, one of a series of the Department of Entomology and Nematology, UF/IFAS Extension. Original publication date July 2002. Revised August 2005, 2006. Revised September 2007, March 2010, June 2013, and February 2017. Deaccessioned July 2021.